MEDIA PEMBELAJARAN BAHASA INDONESIA DI SD/MI - Ade Arif Hilmansyah; Agni Nurul Janah; Anggi Febrianti; Nurfitria (Bajang Institute, 2024)
Indonesian plays a very important role in the social, intellectual and emotional development of students. Indonesian language learning is directed at improving students' ability to communicate well, correctly and precisely in writing and orally. However, the lack of creative methods and open media makes students bored in participating in the teaching and learning process in class. Therefore, this research will explain how media is used in the teaching and learning process in the classroom. This research uses the literature study method, namely research activities whose sources are libraries or books, reading and taking notes and managing research materials. Based on research, it can be concluded that the presence of media in the teaching and learning process can make it easier for students to understand learning material independently.